2020
DOI: 10.1002/ajmg.a.61932
|View full text |Cite
|
Sign up to set email alerts
|

Inherited intragenic PBX1 deletion: Expanding the phenotype

Abstract: PBX1 encodes the pre‐B cell leukemia homeobox transcription factor, a three amino acid loop extension (TALE) homeodomain transcription factor, which forms nuclear complexes with other TALE class homeodomain proteins that ultimately regulate target genes controlling organ patterning during embryogenesis. Heterozygous de novo pathogenic variants in PBX1 resulting in haploinsufficiency are associated with congenital anomalies of the kidneys and urinary tract, most commonly renal hypoplasia, as well as anomalies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Remarkably, genetic PBX1 alterations are rarely found to be familial. In the literature, only two instances of parental transmission have been reported [ 9 , 10 ], whereas all other cases are described as being de novo (29/31) (Table 1 ), although low-grade mosaicism in the parents cannot fully be excluded without more sensitive sequencing techniques, such as NGS.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, genetic PBX1 alterations are rarely found to be familial. In the literature, only two instances of parental transmission have been reported [ 9 , 10 ], whereas all other cases are described as being de novo (29/31) (Table 1 ), although low-grade mosaicism in the parents cannot fully be excluded without more sensitive sequencing techniques, such as NGS.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty patients with heterozygous pathogenic mutations and partial or complete heterozygous deletions of PBX1 have been reported in the literature (Alankarage et al, 2020; Bertoli‐Avella et al, 2021; Eozenou et al, 2019; Fitzgerald et al, 2021; Fromer et al, 2014; Heidet et al, 2017; Le Tanno et al, 2017; Riedhammer et al, 2017; Slavotinek et al, 2017), and 10 additional patients are reported in the ClinVar, DECIPHER, and HGMD databases. Their clinical data are summarized in Table 2.…”
Section: Pbx1 Variations In Humansmentioning
confidence: 99%
“…To date, 17 patients have been reported with whole or partial deletions of PBX1 (Fitzgerald et al, 2021; Heidet et al, 2017; Le Tanno et al, 2017) of whom 3 were siblings (Fitzgerald et al, 2021). The size of these deletions ranged from 37 kb (Fitzgerald et al, 2021) to 18 Mb (patient 398083 from DECIPHER).…”
Section: Pbx1 Variations In Humansmentioning
confidence: 99%
See 2 more Smart Citations